The Effect of Proprioceptive Training on Technical Soccer Skills in Youth Professional Soccer - Meriç Eraslan; Alper Cenk Gürkan; Serhat Aydın; Musa Şahin; Seyfullah Çelik; Mehmet Söyler; Tolga Altuğ; Mustafa Alper Mülhim (Medicina)
Background and Objectives: This study analyzes the effects of proprioceptive training on the physical fitness and soccer-specific technical skills of young professional soccer players. Materials and Methods: Twenty-eight male professional soccer players from the Türkiye Football Federation’s Third League, aged 20.46 ± 1.60 years (average), participated voluntarily. Body composition was assessed with the Inbody270 bioelectrical impedance analyzer, while agility and maximal VO2 cardiorespiratory fitness were measured using the ChronoJump smartspeed mat. Soccer-specific technical skill assessments were also conducted. Data were analyzed using SPSS 22, with paired sample t-tests for comparisons, Cohen’s d test for effect size, and repeated measures two-way ANOVA for interaction effects (group × time). Eta squared (η2) values were reported for effect size. A 95% confidence level and p = 0.05 were used. Results: Proprioceptive training significantly improved body fat percentage (p < 0.05; η2 = 0.006) and soccer-specific technical skills, including free juggling (p < 0.05; η2 = 0.302), alternating foot juggling (p < 0.05; η2 = 0.271), right foot juggling (p < 0.05; η2 = 0.250), and shooting performance (p < 0.05; η2 = 0.513). Conclusions: A 12-week proprioceptive training program, when incorporated into soccer practice, significantly enhances soccer-specific technical skills and reduces body fat percentage.